Reproductive biology and potential distribution of Ficus pringlei (Moraceae), a microendemic New World species - Rojas-Cortés, Ángela P.; Cuervo-Robayo, Ángela P.; Cornejo-Tenorio, Guadalupe; Ibarra-Manríquez, Guillermo (Instituto de Ecología, A.C., 2022)
Background and Aims: One of the most diverse and ecologically important tree genera in the tropics is Ficus. The characterization of developmental phases and morphological changes of its syconium is essential for facilitating pollination and dispersal studies, but only a few species in the Americas have been characterized. Ficus pringlei is endemic to Mexico for which detailed information on the potential distribution and reproductive aspects are lacking. The aims of this study were to describe syconia development, determine the type of pollination, and detect areas of potentially suitable environments for establishing F. pringlei. Methods: Syconia were collected to describe their development phases. The syconia and its pollinating wasps were fixed in alcohol for processing and described using scanning electron microscopy. Ecological niche models were used to predict areas with suitable environments to locate F. pringlei. Key results: The syconium changed in size, color, consistency, and shape of the ostiole over the course of its developmental phases, particularly in stages that were most critical for their interaction with pollinators and dispersers. Syconia development was asynchronous at both the within- and between-individual level in the sampled population. Ficus pringlei is actively pollinated. The predicted suitable distribution area for this species was concentrated mainly in the tropical dry forests of the states of Jalisco and Michoacán. The most important variable to explain the potential distribution model for F. pringlei was the seasonality of temperature, which had higher values in areas north of the Trans-Mexican Volcanic Belt. Conclusions: The developmental phases of this species are consistent with those described previously for other monoecious species. Ficus pringlei is only distributed in western Mexico, mainly in tropical dry forests, and is barely registered in Protected Areas. Therefore, it is essential to establish strategies for its conservation.